Enhanced separation and analysis procedure reveals production of tri-acylated mannosylerythritol lipids by Pseudozyma aphidis. (1st November 2016) - Goossens, Eliane; Wijnants, Marc; Packet, Dirk; Lemière, Filip
Abstract: Mannosylerythritol lipids (MELs) are one of the most promising biosurfactants because of their high fermentation yields (>100 g l −1 ) and during the last two decades they have gained a lot of attention due to their interesting self-assembling properties and biological activities. In this study, MELs were produced by fed-batch bioreactor fermentation of rapeseed oil with Pseudozyma aphidis MUCL 27852. This high-level MEL-producing yeast secretes four conventional MEL structures, -A, -B, -C and -D, which differ in their degree of acetylation. During our research, unknown compounds synthesized by P. aphidis were detected by thin-layer chromatography. The unknown compounds were separated by flash chromatography and identified as tri-acylated MELs by high-performance liquid chromatography tandem mass spectrometry (HPLC–MS/MS). The third fatty acid chain on the tri-acylated MELs was positioned on the primary alcohol of the erythritol moiety and comprised long-chain acids, mainly oleic and linoleic acid, which are not found in conventional di-acylated MELs. Furthermore, the LC–MS analysis time of conventional MELs was reduced to almost one-third by switching from HPLC–MS/MS to ultraperformance liquid chromatography tandem mass spectrometry (UPLC–MS/MS). Provided optimization of the fermentation yield, P. aphidis could be an interesting novel producer of tri-acylated MELs and, thereby expand the supply and applicability of biosurfactants.